Gymnastics Improve Quality Of Life - Endang Sri Wahyuni; Retna Febri Arifiati (Poltekkes Kemenkes Surakarta, 2021)
ABSTRACT Background: The increase in the number of elderly people needs to be balanced with increased expectations and quality of life. One of the causes of the low quality of life of the elderly is influenced by a lack of physical activity. Efforts that can be made to improve the quality of life of the elderly are by doing physical activity or exercising regularly. This study aims to determine the effect of physical activity on the quality of life of the elderly. Methods: This type of research is quantitative, pre-experimental with one group pretest-posttest design, using purposive sampling technique. The research instrument was the WHOQOL-BREF questionnaire. The research subjects were 30 people. Data analysis used the Wilcoxon test. Results: As many as 80% of the subjects were in the age range 66-74 years, 26 subjects were women (53.3%), the latest education was dominated by Bachelor 43.4%. As many as 76.7% are retired civil servants, 70% still have a partner, 26.7% live with a partner and children, and 66.7% are healthy elderly without a history of disease. The results show a positive value and an increase in the mean in each domain. The asymptotic significance values of the pre-post Wilcoxon ranking test on the domain of physical and environmental conditions were 0.000 and 0.003 on psychological conditions and social relationships. Conclusion: The provision of physical activity interventions in the form of flexible exercise for the elderly has a significant impact on improving the quality of life of the elderly.